Synthesis, Crystal Structure and Magnetic Properties of a Novel Heterobimetallic Rhenium(IV)–Dysprosium(III) Chain. Issue 24 (27th April 2015) - Pejo, Carolina; Guedes, Guilherme P.; Novak, Miguel A.; Speziali, Nivaldo L.; Chiozzone, Raúl; Julve, Miguel; Lloret, Francesc; Vaz, Maria G. F.; González, Ricardo
Abstract The use of the mononuclear rhenium(IV) precursor [ReBr5(H2pydc)]− (H2pydc=3, 5‐pyridinedicarboxylic acid) as a metalloligand towards dysprosium(III) afforded the first heterobimetallic ReIV–DyIII complex. Crystal structures and static and dynamic magnetic properties of both rhenium‐containing species are reported herein. The 5d–4f compound shows an extended 1D structure and the AC magnetic measurements reveal frequency dependence at low temperature suggesting slow relaxation of the magnetization.